Promoting Cultural and Language Diversity in World Languages Classes - Maganda, Dainess M. (Advances in Social Sciences Research Journal, 2025)
In the 21st century, intercultural perspectives in education seeking to foster a sense of understanding around the world have become the norm. This paper examines ideas regarding the meaning and role of language ideology in the quest to promote linguistic diversity in today’s world, starting with classrooms. The author offers practical ideas on how teachers in general, and specifically teachers of world languages, culture and literature can cultivate an appreciation for varied languages in their classrooms and underscore ways to help students see the interaction between language, culture, literature through an intercultural education perspective. The author will also highlight challenges teachers are likely to face while offering ideas to address them.